Exploring the Impact of Demographic Characteristics of Top Management Team on Earning Management: The Case of Chinese-Listed Manufacturing Companies - Chen, Yawen (2020)
This study examines the relationship between the demographic characteristics of the top management team (TMT) and earnings management by the use of 1307 Chinese-listed manufacturing companies from China Stock Market and Accounting Research, covering the period 2014-2018. The demographic characteristics of the TMT is measured by the use of four factors: gender, age, financial work experience and educational level. The abnormal cash flow from operations, abnormal production cost, abnormal discretionary cost and a comprehensive proxy of the sum of these three are employed in the estimation of real earnings management, which is a proxy for earnings management. The variables controlled by this research include leverage, company size, book-to-market ratio, return on equity and sales growth. The findings in this study show that the gender, age and financial experience of top managers have no significant impact on earnings management. However, the average educational level of top managers is significantly negatively correlated with earnings management meaning that top managers with higher education may participate less in earnings management activities. These results are partially consistent with the prediction of the Upper Echelons Theory that the TMT’s demographic characteristics as a measure of the potential cognition and behaviour of individuals and teams, thus influencing the earnings management decisions of the company. These results have implications for various stakeholders in corporate financial reporting and also provides insights for those who select and train top managers.